Life satisfaction predicts positive workplace outcomes among Filipino guidance counselors - Mateo, Niño Jose (Animo Repository, 2018)
The study tested the broaden-and-build theory of positive emotions (Fredrickson, 1998; 2003) in the field of counseling practice. The researchers hypothesized that counselors’ life satisfaction would predict outcomes relevant in practice: counseling self-efficacy, emotional awareness, and flow state. Participants (n = 137) completed measures of counseling self-efficacy, flow state, life satisfaction, and emotional awareness. Age, gender, civil status, and degree earned were identified as covariates and their effects were controlled in the regression analyses. Findings revealed that life satisfaction positively predicted flow state and emotional awareness. Counselors who expressed greater satisfaction with their lives seem to see the counseling experience as rewarding and are more attuned to their emotions. This finding is consistent with the key postulate of broaden-and-build theory on the beneficial consequences of positive affect on psychological resources.